Analisis produktivitas departemen servis pada PT TI dengan Metode Objective Matrix (Omax) - Maulana, Eko; Perdana, Surya (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2020)
PT IT is a company engaged in the air system facilities industry, the company experienced an up-and-down phase in the company’s productivity in 2019. To deal with an existing problem in the company used the Objective Matrix (Omax) method. The method will discuss the performance criteria that have a weight value to be used as a measure of productivity in the company and the criteria that will be combined into one in a particular working group into a matrix. The result of this study is that the company experienced an up-and-down phase that in June 2019 experienced an increase in demand in maintenance chiller jobs with low main hours. Meanwhile, in May 2019 the company experienced a decrease caused by chiller units done by technicians quite a bit and the number of complaints from customers because they were dissatisfied with the workers worked by technicians. In addition, it is also known that some criteria are used to measure the value of productivity weights such as man hours criteria, water criteria, electricity criteria, material criteria and quality criteria. As for the criteria that contribute less in productivity improvement that contributes to the decrease in productivity of the company is the criteria 3 namely the use of water energy with a score of 35. From the results obtained, the company will provide counseling to each employee at the time of the evaluation of work.